Evaluation of the federal hospital atlas in the context of the hospital reform 2024: a critical analysis of the healthcare provision in German hospitals - Jonas Roos; Theresa Isabelle Wilhelm; Ron Martin; Kristian Welle; Elio Assaf; Robert Kaczmarczyk (Archives of Public Health)
Abstract Background In the context of the ongoing German hospital reform, the newly introduced Federal Hospital Atlas aims to increase transparency regarding hospital structures and service quality. However, concerns have been raised regarding its completeness and reliability. Understanding regional differences in hospital characteristics—such as ownership type, staffing levels, emergency care provision, and specialization—is essential to assess the current state of healthcare and inform policy decisions. Methods We conducted a cross-sectional analysis of 1,628 hospitals using data from the Federal Hospital Atlas (as of April 2025). Hospitals were categorized by ownership type, region (old vs. new federal states), population density, and specialization. Multivariable regression models—including ordinal logistic and negative binomial regressions—were used to examine associations with nursing staff ratios, emergency care participation, the number of specialized departments, and certifications. Results Among the 1,628 hospitals analyzed, 36.57% were public, 35.27% nonprofit, and 28.16% private. Nonprofit (OR = 0.58, 95% CI [0.46–0.74]) and public hospitals (OR = 0.69, 95% CI [0.55–0.86]) had significantly lower nursing staff ratio categories compared to private hospitals but were more likely to provide emergency care (nonprofit: OR = 3.05, 95% CI [2.27–4.12]; public: OR = 4.81, 95% CI [3.52–6.61]). Trauma and/or orthopedic specialization was associated with higher emergency care participation (trauma: OR = 21.8; both: OR = 38.7) and higher structural differentiation (both: IRR = 3.11 for departments; IRR = 4.94 for certifications). Hospitals in densely populated areas had better nursing staff ratios (OR = 1.38, 95% CI [1.15–1.67]) and more certifications (IRR = 2.86, 95% CI [2.46–3.33]). No significant differences were found between old and new federal states in staffing or emergency care provision. Conclusion The analysis reveals significant differences in hospital facilities and service provision in Germany. Public and non-profit hospitals are more heavily involved in emergency care, but have comparatively lower nursing staff ratio categories. Hospitals specializing in trauma or orthopedic care, as well as those in urban areas, tend to be larger and better equipped. These results point to imbalances and underscore the need for political action to ensure equal access and high-quality hospital care across regions and providers.